Vocational Students’ Engagement In Enhancing Students’ Speaking Skill - Yevi Elok Fortuna; Elih Sutisna Yanto; Fauzi Miftakh (International Journal of Education, Information Technology, and Others, 2021)
Although much research in context of Digital Storytelling in English for Foreign Language teaching has extensively been explored, Digital Storytelling as a strategy for engaging students’ in enhancing students’ speaking skills in social media assisted is rarely mentioned in literature. To fill this void, this study reports findings drawing on a micro-ethnographic classroom research in Digital Storytelling through students’ individual video based project in English speaking classroom using Instagram platform as media for teaching. Further, students are follow five stages in creating Digital Storytelling, there are Introduction to the Digital Storytelling, Scaffolded Creation of Digital Stories, Creation of Digital Stories, Presentation of Digital Stories and uploaded to Instagram, and Reflection. Reported by students’ interviews, reflective journal, and students’ artifacts, students opined that Digital Storytelling in Speaking classroom can engage students while learning English and the Digital Storytelling can enhance students’ speaking skills. The other research finding showed that Digital Storytelling in Instagram-Assisted can boosts students’ motivation and bring students to high of enthusiasm while learning English speaking skill.